The path of the body. ways of meaning in Bharata Natyam - Borraccino, Giulia (E|C, 2020)
This work deals with the question of the methodological approach to the study of dancing art. Semiotics considers the body not only as an instance of enunciation of a language, but as language itself. The object of the analysis will be the Indian dance Bharata Natyam, whose features depend on a rhythmic competence and on the idea of a gestural mimic narration. Using the theory of narrativity and the “canonical passional schema” we will translate a dance performance into a sequence of phases: the ones dancing body faces according to a passionate transformation of the subjects involved in the experience.